2022
DOI: 10.1093/schizbullopen/sgac032
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Patterns Can Distinguish Schizophrenia From the Major Affective Disorders and Healthy Control Subjects

Abstract: Background and hypothesis No objective tests are currently available to help diagnosis of major psychiatric disorders. This study evaluates the potential of eye movement behavior patterns to predict schizophrenia subjects compared to those with major affective disorders and control groups. Study Design Eye movements were recorded from a training set of UK subjects with schizophrenia (SCZ; n=120), bipolar affective disorder (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…The AUC for scanpath length was 0.81, while the AUCs for cognitive function measures ranged between 0.85 and 0.90. These results were similar to the findings of previous studies using desktop-based eye movement measurements, which reported AUCs ranging between 0.77 and 0.89 [20,21,24], and previous studies using paper-based cognitive functioning measurements, which reported AUCs ranging between 0.88 and 0.90 [35,36]. Okazaki et al found that pairing certain cognitive function measures with eye movement measures led to improved performance and robustness in distinguishing patients with schizophrenia from healthy individuals, with an average increase in the AUC of 0.10 compared with eye movement measures alone and 0.05 compared with cognitive function measures alone [29].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The AUC for scanpath length was 0.81, while the AUCs for cognitive function measures ranged between 0.85 and 0.90. These results were similar to the findings of previous studies using desktop-based eye movement measurements, which reported AUCs ranging between 0.77 and 0.89 [20,21,24], and previous studies using paper-based cognitive functioning measurements, which reported AUCs ranging between 0.88 and 0.90 [35,36]. Okazaki et al found that pairing certain cognitive function measures with eye movement measures led to improved performance and robustness in distinguishing patients with schizophrenia from healthy individuals, with an average increase in the AUC of 0.10 compared with eye movement measures alone and 0.05 compared with cognitive function measures alone [29].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with that in previous attempts to establish diagnostic markers for differentiating between patients with schizophrenia and those without schizophrenia using eye movement characteristics [37,38]. However, previous studies indicated mixed results of both cognitive function [39][40][41] and eye movement [21,38,42]. Conducting future studies on transdiagnostic characteristics of multiple modalities is increasingly important.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Very recently St Clair and colleagues 46 applied a multiclass machine-learning model to differentiate patients with schizophrenia, bipolar affective disorder, major depression disorder, and healthy controls on the basis of 98 eye movement symptoms (including several SPEM variables). The model was tested in two validation sets achieving balanced accuracies for schizophrenia patients of 73% and 75%.…”
Section: Discussionmentioning
confidence: 99%